2016
DOI: 10.4025/actasciagron.v38i1.26433
|View full text |Cite
|
Sign up to set email alerts
|

<b>Univariate and multivariate statistical tools for <i>in vitro</i> conservation of citrus genotypes

Abstract: ABSTRACT. This study aimed to evaluate the influence of the growing environment on the in vitro conservation of citrus genotypes obtained from the Active Citrus Germplasm Bank of Embrapa Cassava and Fruit. The study used multivariate statistic tools in order to improve the efficiency in the analysis of the results. Approximately 1-cm of length microcuttings from plantlets derived from ten genotypes previously cultured in vitro were inoculated in test tubes containing 20 mL of WPM culture medium supplemented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In a study for in vitro conservation of the species Laelia anceps Lindl, the mean values for the variable number of sprouts varied between 1.67 and 3.78 at a temperature of 25°C In cassava conservation in vitro, Vieira et al (2015), while using the same culture medium (8S) at a temperature of 22 °C (conservation room) to evaluate the number of green leaves, verified this variable was the one that most influenced plant behavior. Carvalho et al (2016), evaluating the influence of incubation conditions in the conservation in vitro of citrus germplasm, verified differences in the number of green leaves for each temperature tested. Vieira et al (2015), while working with cassava plants in vitro, observed a value of 3.72…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In a study for in vitro conservation of the species Laelia anceps Lindl, the mean values for the variable number of sprouts varied between 1.67 and 3.78 at a temperature of 25°C In cassava conservation in vitro, Vieira et al (2015), while using the same culture medium (8S) at a temperature of 22 °C (conservation room) to evaluate the number of green leaves, verified this variable was the one that most influenced plant behavior. Carvalho et al (2016), evaluating the influence of incubation conditions in the conservation in vitro of citrus germplasm, verified differences in the number of green leaves for each temperature tested. Vieira et al (2015), while working with cassava plants in vitro, observed a value of 3.72…”
Section: Discussionmentioning
confidence: 93%
“…In studies concerning in vitro conservation we seek protocols to establish the reduction of plant metabolism, higher interval between cultivation, lower growth, lower number of senescent leave and higher number of green leaves (Carvalho et al 2016, Vieira et al 2015. Thus, it is important to perceive the association between these variables and to use it as a way to identify minimum growth, in order to preserve plant viability in multiplication, recovery and rescue processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows the fact that the conditions for the development of a species can vary among genotypes, as reported by Grattapaglia and Machado (1998), since each species or clone presents unique characteristics, determined by genetic factors. In general, we can say that WPM is a suitable medium for cloning citrus varieties, because it has been used for in vitro establishment of hundreds of citrus accessions (Carvalho et al, 2016), involving various Citrus species and related genera, such as Poncirus (Raf. ), Fortunella (Swingle), Microcitrus (Swingle) and Eremocitrus (Swingle).…”
Section: Resultsmentioning
confidence: 99%
“…Wood Plant Medium (WPM) is a basic cultivation medium that has been used for the in vitro establishment of Citrus Germplasm Active Bank of the Embrapa Cassava and Fruits, as it provides very promising results in the multiplication of several citrus genotypes (Carvalho, Souza, Santos, Soares Filho, Ledo, & Souza, 2016). The objective of the work was to propagate rootstocks of agronomic interest by means of in vitro cultivation using the WPM culture medium.…”
Section: Introductionmentioning
confidence: 99%